1999
DOI: 10.1046/j.1365-2648.1999.01207.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and outcomes: agendas, presuppositions and power

Abstract: This paper explores philosophical and methodological issues involved in determining 'What counts as making a meaningful difference?'--the fundamental question in health outcomes research and evidence-based practice. Eight diverse stakeholders are identified along with the competing agendas they bring to the debate. The power to define what counts as meaningful change in health status is typically rooted in disciplinary socialization, linguistic traditions and an orthodox consensus that circumscribes acceptable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 62 publications
0
41
0
Order By: Relevance
“…However, it may also be seen as a strength of this study that the results obtained can be directly applied to the typical clinical situation. 80 This study has also demonstrated that at four months CA, the AIMS only detected two (17%) of the 12 infants with CP from the preterm group, highlighting that its use in the detection of preterm infants with abnormal motor development at four months CA may be limited. This is contradictory to the findings of Darrah et al 57 The use of additional or alternative motor assessments (eg, the TIMP) in future studies is recommended.…”
Section: Study Limitationsmentioning
confidence: 84%
“…However, it may also be seen as a strength of this study that the results obtained can be directly applied to the typical clinical situation. 80 This study has also demonstrated that at four months CA, the AIMS only detected two (17%) of the 12 infants with CP from the preterm group, highlighting that its use in the detection of preterm infants with abnormal motor development at four months CA may be limited. This is contradictory to the findings of Darrah et al 57 The use of additional or alternative motor assessments (eg, the TIMP) in future studies is recommended.…”
Section: Study Limitationsmentioning
confidence: 84%
“…7 -10 Indeed, the public are rarely included in the debate about what constitutes 'meaningful health outcomes'. 11 A number of studies propose the importance of an 'insider perspective' for considering outcome i.e., that perspective which is derived from the experience of the person living with a disability, focuses on psychosocial impacts concerning perceptions of the self, relationships with others and life meaning. 10, 12 -15 At least on some levels, this contrasts starkly with a more stereotypically biomedical view (or 'outsider perspective') where the concern is more disease focused aiming to determine diagnosis and intervention at the level of impairment or perhaps disability.…”
Section: Introductionmentioning
confidence: 99%
“…A further positioning occurs through disciplinary socialization to particular research approaches (Ray, 1999). Disciplinary socialization occurs when a researcher receives his or her research training within a disciplinary culture or setting where a particular approach is well known and accepted.…”
Section: Theoretical Positioningmentioning
confidence: 99%